Cyclical inflation divergence and different labor market institutions in the EMU - Alessia Campolmi; Ester Faia (European Central Bank (ECB), 2006)
This paper relates the size of the cyclical inflation differentials, currently observed for euro area countries, to the differences in labor market institutions across the same set of countries. It does that by using a DSGE model for a currency area with sticky prices and labor market frictions. We show that differences in labor market institutions account well for cyclical inflation differentials. The proposed mechanism is a supply side one in which differences in labor market institutions generate different dynamics in real wages and consequently in marginal costs and inflations. We test this mechanism in the data and find that the model replicates well the empirical facts.
Keywords: E52; E24; 330; cyclical inflation divergence; EMU; labor market institutions; Konjunktur; Räumliche Verteilung; Eurozone; Arbeitsmarkt; Institutionelle Infrastruktur; EU-Staaten